New species of Asterina and Balladyna (black mildew fungi) from Mahabaleshwar, Maharashtra, India - Bhise, Mahendra R.; Patil, Chandrahas R.; Salunkhe, Chandrakant B.; Kambhar, Sidanand V. (Phytotaxa, 2021)
Two new black mildew fungal species, Asterina rubiacearum sp. nov. and Balladyna canthiigena sp. nov., which infect the leaves of Canthium dicoccum var. umbellatum (Rubiaceae) are described from Mahabaleshwar, Maharashtra (India). Taxonomic descriptions, photomicrographs, line drawings and comparative account of close associate species are provided.